Social protection amid a crisis: New evidence from South Africa’s Older Person’s Grant - Alloush, Mo; Bloem, Jeffrey R.; Malacarne, J. G. (Oxford University Press, 2024)
This study estimates the effects of South Africa’s Older Person’s Grant on well-being amid the COVID-19 pandemic. With household-level data collected before and during the pandemic, it leverages the age-eligibility threshold of the grant to estimate its effects on households in both periods. Prior to the pandemic, this study finds that grant receipt substantially improves economic well-being and decreases adult hunger at the household level. During the first 18 months of the pandemic, this study finds larger effects on both economic well-being and hunger than prior to the pandemic. In particular, recipient households were less likely to report running out of money for food and hunger among either adults or children. These results, which are stronger when pandemic-related lockdown policies are in place and for more vulnerable households, provide critical insight into the effectiveness of one of the world’s most well-known cash-transfer programs during a massive global health crisis.